Mechanical behaviour of aramid sandwich weft knitted fabrics - Ciobanu, Ana-Ramona (2012)
High-performance fibres are used for their inherent mechanical properties in various applications in technical field. Knitted fabrics with simple to complex structures have been studied for their mechanical behaviour. The sandwich fabrics made from aramid fibres are lightweight materials with excellent strength-to-weight properties exhibiting good behaviour in relation to shear, impact and energy absorption, due to the orientation of fibers in the third dimension. This paper presents a study on the influence of the high performance yarns on the mechanical behaviour of sandwich weft knitted fabrics. The tensile behaviour of the raw materials is analyzed based on experimental data. The sandwich knitted fabrics considered for the study are produced on an electronic flat knitting machine Stoll CMS 320 TC, E 10, using Kevlar® and Kevlar® with Inox yarns.